Diagnostic performance of gadofosveset-enhanced axillary MRI for nodal (re)staging in breast cancer patients: results of a validation study. Issue 2 (February 2018) - van Nijnatten, T.J.A.; Schipper, R.J.; Lobbes, M.B.I.; van Roozendaal, L.M.; Vöö, S.; Moossdorff, M.; Paiman, M.-L.; de Vries, B.; Keymeulen, K.B.M.I.; Wildberger, J.E.; Smidt, M.L.; Beets-Tan, R.G.H.
Abstract : Aim: To evaluate diagnostic performance of gadofosveset (GDF)-enhanced magnetic resonance imaging (MRI) in addition to T2-weighted (T2W) MRI for nodal (re)staging in newly diagnosed breast cancer patients. Materials and methods: Ninety patients underwent axillary T2W- and GDF-MRI. Two radiologists independently scored each lymph node; first on T2W-MRI, subsequently adjusting their score on GDF-MRI. Diagnostic performance parameters were calculated on node-by-node and patient-by-patient validation with histopathology as the reference standard. Furthermore, learning curve analysis for reading GDF-MRI was performed. Results: In patient-by-patient validation, overall reader performances for T2W- and GDF-MRI were similar with area under the receiver operating characteristic curves (AUC) of 0.75 and 0.77 ( p= 0.731) for reader 1 and 0.79 and 0.72 ( p= 0.156) for reader 2. For node-by-node validation, AUC values of T2W- and GDF-MRI were 0.76 and 0.82 ( p= 0.018) and 0.77 and 0.77 ( p= 0.998) for reader 1 and 2. The AUC for reader 1 was 0.71 for first one-third of nodes evaluated, improving to 0.80 and 0.95 for the next and last one-third, respectively. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) improved from 38%, 89%, 56%, and 79% to 60%, 93%, 64%, and 92%. The AUC of reader 2 improved from 0.69 to 0.79. Conclusion: The present study confirmed that GDF-MRI, in addition to T2W-MRI, has potential as a non-invasive method for nodal (re)staging in breast cancer. Highlights: GDF-MRI can differentiate between benign and malignant axillary lymph nodes. A learning curve for reading GDF-MRI was observed for one reader. After the assessment of 176 nodes, NPV of GDF-MRI increased to 92%. Prevalence of lymph node metastases was 28.5% in this cohort.